Efek Selang Bekerja terhadap Perubahan Bobot Badan dan Penggunaan Pakan pada Sapi Peranakan Ongole - N. Usri (Buletin Ilmu Makanan Ternak, 1991)
The aim of this study was to investigate if working period could affect growth and feed consumption of Ongole cross cattle. Twenty four heifers were used in a completely randomized experiment that consisted of 4 working patterns: not working, one day working + two days rasting, one day working + one day rasting and working every day. Each treatment was replicated 6 times. All worked animals pulled a 45 kg-burden from 7.00-11.00 a.m. With 30 minutes break (8.00-8.30 a.m.). All animals were fed with native grasses ad libitum + 0.75 kg concentrate per day. Working pattern did not affect weight gain as well as feed efficiency. The average daily gain was 0.27 kg and the feed efficiency was 0.0649 (gain/consumption). However, it significantly (p<0.05) influenced the feed consumption, feed cost and water consumption. The mean value of the feed consumption, feed cost and water consumption were 4.22 kg, Rp. 264.17, and 4.17 kg, respectively.